PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP KINERJA TENAGA MEDIS YANG DIMEDIASI OLEH KEPUASAN KERJA PADA RSUD dr. ZUBIR MAHMUD ACEH TIMUR - Khairullah Putra Aksa; Yurnalis Yurnalis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
This study aims to determine the effect of Democratic Leadership Style on the Performance of Medical Personnel Mediated by Job Satisfaction at RSUD dr. East Aceh Zubir Mahmud. There are 5 indicators discussed in the Democratic Leadership Style variable, 12 indicators in the job satisfaction variable, and 6 indicators in the performance variable. Data were obtained through a survey of 42 people as a sample representing the study population. The data analysis method used is Statistical Product and Service Solutions (SPSS). The results of the study found that Democratic Leadership Style and Job Satisfaction have an effect on performance. The results of the study also found that the variable Job Satisfaction mediates between Democratic Leadership Style and Performance.